Trajectories of perceived exertion and pain over a 12-week neuromuscular exercise program in patients with knee osteoarthritis. Issue 11 (November 2020) - Primeau, C.A.; Birmingham, T.B.; Moyer, R.F.; O'Neil, K.A.; Werstine, M.S.; Alcock, G.K.; Giffin, J.R.
Summary: Background: Exercise programs rely on the overload principle, yet patients with knee osteoarthritis (OA) may not adequately progress exercises due to fear of exacerbating symptoms. Objective: To describe trajectories for perceived exertion and exercise-induced knee pain during a neuromuscular exercise program for patients with knee OA. Design: Participants with knee OA completed a 12-week neuromuscular exercise program consisting of weekly supervised sessions plus home exercises. During each supervised session, the Borg's rating of perceived exertion (RPE; 6 = no exertion, 20 = maximal exertion) and knee pain (pre, post, max) using Numeric Rating Scales (NRS; 0 = no pain, 10 = worst imaginable pain) were completed. Mean changes in RPE and pain from weeks 1–12 were calculated. Mixed effects regression was used to investigate trajectories over time (weeks) for RPE, and maximum pain (pre-to-max) and pain-change (pre-to-post) during exercise. Results: 56 patients (95%) completed the program. From week 1–12, RPE increased by 2.6 (95%CI, 1.7 to 3.5), from ' somewhat hard ' to ' very hard ', while max pain decreased by 1.0 NRS (95%CI, 0.5 to 1.3) and pain-change decreased by 0.9 NRS (95%CI, 0.4 to 1.3). Linear mixed effects regression showed a quadratic increase for RPE over time until between weeks 9 and 10, then RPE plateaued. Maximum pain decreased linearly over time. Pain-change showed a quadratic decrease over time until approximately week 9, then pain-change plateaued. Conclusions: In patients with knee OA participating in a 12-week neuromuscular exercise program, perceived exertion during exercise progressed from ' somewhat hard' to ' very hard ' at 9 weeks, while exercise-induced knee pain decreased. Patients were able to work harder while experiencing decreases rather than increases in pain.